Social Advertising as a Mechanism of Volunteering - Bilych, Iryna (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
In the article the social advertisement is presented as a mechanism of activation of volunteerism in Ukraine. The basic approaches to the definition of "social advertising" are characterized. The pattern of the social advertisement’s impact upon the potential volunteers is shown and the main directions in the subject field which may facilitate the development of criteria for effective social advertisement of volunteer activities are presented. The main aspects of social advertisement that can affect the development of volunteerism are analyzed.